Increased Neutrophil Count Related to Bleeding Volume in Intracerebral Hemorrhage Cerebrovascular Accident - Pratitan, Alifta Ridzki; Pambudi, Pagan; Illiandri, Oski (Universitas Muhammadiyah Semarang, 2024)
Background: Cerebrovascular accidents (CVA) was increasing per year. In Indonesia reached 550.000 cases per year. Ten to fifteen percent are types of CVA bleeding (CVA-B). Death and disability as complications of CVA-B are more often compared to an ischemic type. Early diagnosis of CVA-B is key to decreasing it’s complications. Unfortunately, diagnosis of early CVA-B requires excellent effort and spending more expense when using an advanced CT scan. Previous research has shown a relationship between leucocyte count and CVA, but there is no adequate data relating leukocyte count and mean arterial pressure (MAP) with bleeding volume in CVA-B patients.Objective: This study aimed to answer whether Leukocyte count combined with MAP can be a choice to diagnose CVA-B at an early stage.Methods: Analytic observational research was conducted with a cross-sectional approach. The population of this study was all patients with CVA intracerebral bleeding at Ulin Hospital of Banjarmasin. The patient's medical records and CT scans were used to assess the bleeding volume. The number of leukocytes and the patient's mean arterial pressure were tabulated and analyzed to their relationship with bleeding volume.Results: In this study, there was a significant relationship between the number of leukocytes and the volume of intracerebral hemorrhage (r=0.801, p=0.000). There was no significant relationship between the MAP and the volume of intracerebral hemorrhage (r=0,17, p=0,361)Conclusion: There is a strong relationship with a significant relationship between the number of leukocytes and the volume of bleeding in patients with intracerebral hemorrhage but no relationship with MAP.